Threatened oceans - Tesar, Jenny E. (New York Facts on File, 1991)
Explores the vital importance of ocean ecosystems and resources and focuses on how fishing, dumping, oil spills, and other human influences endanger the marine environment.
Keywords: Oceanography -- Juvenile literature; Ecology; Marine ecology; Marine resources conservation; Ocean